Post‐traumatic stress symptomatology and adjustment of medical oncology practice during the COVID‐19 pandemic among adult patients with cancer in a day care hospital. Issue 24 (16th August 2021) - Joly, Florence; Rigal, Olivier; Guittet, Lydia; Lefèvre‐Arbogast, Sophie; Grellard, Jean‐Michel; Binarelli, Giulia; Lange, Marie; Rieux, Chantal; Fernette, Marie; Tron, Laure; Gernier, François; Travers, Romain; et al.
Abstract : Background: The COVID‐19 pandemic may induce post‐traumatic stress disorder (PTSD) symptoms among patients with cancer, who also face adaptations to their treatment. The authors assessed the occurrence of PTSD symptoms, investigated pandemic‐induced adjustments in medical oncology practice in patients with cancer, and explored risk factors for PTSD and the association between PTSD symptoms, insomnia, and quality of life (QoL). Methods: This prospective French study was conducted in patients with solid/hematologic tumors who were receiving medical treatment in the day care departments of 2 cancer centers during the lockdown. Adjustments to medical oncology practice were collected from medical records. PTSD (measured using the Impact of Event Scale‐Revised), insomnia (measured using the Insomnia Severity Index), QoL (measured using the Functional Assessment of Cancer Therapy‐General instrument), and cognitive complaints (measured using the Functional Assessment of Cancer Therapy–Cognitive Function instrument) were collected through validated questionnaires. Results: Clinical data and questionnaires were available for 734 and 576 patients, respectively. The median patient age was 64 years, and 69% of patients were women. Twenty‐one percent of patients had PTSD. Twenty‐seven percent (95% CI, 23%‐30%) had an adjustment in their medical oncology program, including adjournments (29%), treatment interruptions (16%), modified treatment plans (27%), or adapted monitoring (27%). Women and patients experiencing an adjustment in oncology practice had a higher odds of PTSD (odds ratio= 2.10 [95% CI, 1.07‐4.14] and 1.65 [95% CI, 1.03‐2.63]; P  < .05). PTSD symptoms were correlated with worse scores for QoL, cognition, and insomnia. Conclusions: Twenty‐one percent of patients with cancer experienced PTSD symptoms associated with poor QoL during the first COVID‐19–induced lockdown. Medical oncology practice was adjusted in approximately one‐quarter of patients and was associated with the occurrence of PTSD symptoms. Psychosocial support should be offered in cancer centers to promote emotional resilience and avoid PTSD symptoms in patients. Abstract : Post‐traumatic stress disorder symptomatology occurred in 21% of patients with cancer during the first lockdown due to COVID‐19, was more frequent among women, and was associated with adjustment in medical oncology treatments. Caregivers should pay special attention to the psychological needs of patients with cancer to prevent or manage post‐traumatic stress disorder symptoms.